Poverty and Inequality in the Maldives - World Bank (World Bank, Washington, DC, 2019)
Around the world, countries use a wide variety of poverty measurement methodologies. A common method used to measure poverty is based on levels of consumption - a person is considered poor if his or her consumption level falls below some minimum level necessary to meet basic needs. This note therefore aims at briefly laying out the methodological framework of measuring poverty in the Maldives using a relative poverty line and presents findings of applying the poverty concepts in the context of the Maldives. For the purpose of this note, poverty is the pronounced deprivation in well-being defined as whether households or individuals have enough resources or abilities to meet their needs. Poverty is also multidimensional in nature and can include low incomes and the inability to acquire the basic goods and services necessary for survival with dignity but also low levels of health and education, poor access to clean water and sanitation, inadequate physical security, lack of voice, and insufficient capacity and opportunity to better one’s life.